Analysis of voltage drop causes at SMK Ponpes Manbaul Ulum Cirebon - Lutfi Zulfiyan (Journal of Emerging Innovations in Engineering, 2026)
This study aimed to identify the causes, evaluate, and quantify the magnitude of voltage drop at SMK Ponpes Manba'ul’Ulum Cirebon. A descriptive quantitative approach using a single case study strategy was applied. Data were collected from PT PLN ULP Sumber, Cirebon, and through direct field measurements using a Digital Earth Tester, Digital Insulation Tester, and monitoring of a three-phase kWh meter. The findings revealed that the main cause of voltage drop was transformer overload at Distribution Substation CKPB, with a loading level of 91.20%, exceeding the 80% limit specified by the Indonesian Electricity Supply Standard (SPLN). Additional contributing factors included a 710-meter conductor length with a 70 mm² cross-sectional area, inter-phase load imbalance (I₁ = 105 A, I₂ = 149 A, I₃ = 141 A), and insulation resistance anomalies detected at several test points (0 MΩ at N-T, T-G, and N-G). Before transformer uprating, the voltage drop reached 28.49 V (14.92%), exceeding the SPLN 72:1987 tolerance range of 5–10%. After uprating the transformer capacity from 100 kVA to 160 kVA combined with load splitting, the voltage drop decreased to 13.57 V (6.33%) and transformer loading declined to 57.10%.